Soil macrofauna in four farms in conversion to ecological production in the Municipality Cruces, Cuba - Fernandez Terry, Itania Maria; Castellanos Gonzalez, Leonides; Fuentes Gallardo, Mario; Cairo Cairo, Pedro; Melo Prado, Renato de [UNESP] (Univ Central Marta Abreu Las Villas, 2015)
The research was conducted in four farms Agricultural Company Bad weather town of Cruces, Cienfuegos, who are in the process of conversion to ecological production. In order to evaluate the macrofauna populations present in the soil at different depths in the same areas of fruit trees, where crops are interspersed developed. In each farm were assessed total of individuals for which samples were taken in two seasons, rainy season and dry seasons. Soil macrofauna on the farms studied consisted of representatives of three Phyllum, five classes, 12 orders and 37 species. The largest populations of insects, mites, annelids, molluscs and myriapods were quantified in Las Carolinas and The Mahogany, as long favored by the phase transformation, higher organic matter content and pH neutral. Populations of annelids, myriapods and mites abounded more in the dry season and insects in the rain. Mite populations were large between 10 and 20 cm of the soil surface, the insect was similar but also abounded in litter; however, annelids, molluscs millipedes and showed no preference for a certain depth.
Keywords: Agroecological farm; soil; macrofauna